Aptamer-dependent full-length cDNA synthesis by overlap extension PCR - Yasumasa Mitani; Takayuki Nakayama; Matthias Harbers; Yoshihide Hayashizaki (BioTechniques)
Sequencing of the human genome in combination with computational annotation has provided tremendous data on predicted genes. However, for most of them, no corresponding cDNAs are available yet. Furthermore, even where cDNA clones were obtained, gene transcripts often have many different splice variants that are not covered by current gene collections. For direct synthesis of cDNA clones corresponding to predicted genes, new splice variants, or any other gene of interest, we established optimal PCR conditions for the direct amplification of exons from genomic DNA, which require a specific Taq aptamer. PCR products comprising differently tagged exons were concatenated by overlap extension into full-length cDNAs. To prove the effectiveness of the approach, the 1900-bp full-length open reading frame of the human mitochondrial aldehyde dehydrogenase (ALDH2) gene was synthesized in a two-step reaction comprising all 13 exons. Thus, our conditions are of general value for in vitro synthesis of cDNAs and alternative splice variants from genomic DNA.